The relationship between serum vitamin D levels with infection and severity of Covid-19 Symptoms in women and children: A systematic review study - Rasoul Rahmani; Yeganeh Lexian (Mashhad University of Medical Sciences, 2022)
Introduction: Serum levels of vitamin D on the development and exacerbation of symptoms of Covid-19 disease have been expressed and discussed in several studies. The present study was performed aimed to systematically review the studies performed on the relationship between serum level of vitamin D with the incidence and severity of Covid-19 symptoms disease in women and children.Methods: In this systematic review study, to obtain the related studies, the English databases of Pubmed, Scopus and Web of Science were searched up to April 4, 2021 with the English keywords of Vitamin D and Covid-19 with combination of operators "AND" and "OR". Inclusion criteria were: cohort articles, case-control or cross-sectional and English language articles and the study population were women or children. The quality of articles was assessed using the Strobe checklist. Based on the Strobe criteria, studies which scored moderate and good in the assessment were included in the study.Results: Out of 315 articles, 23 qualified articles were reviewed. In these studies, the association between serum vitamin D levels and the incidence, severity, and mortality of Covid-19 was assessed. Two studies included the population of children and 21 studies of women.Conclusion: Low serum levels of vitamin D are significantly associated with an increase in the incidence of Covid-19 and the severity of the disease, but this relationship with the mortality rate from the disease provides contradictory results in several studies; therefore, more studies in this field are necessary to achieve more definite results, especially in children.